Taylor Swift’s Speech at New York University: Revealing Interpersonal Meaning - Novita Nurul Kholilah; Afiifah Al Rosyiidah (Universitas Sebelas Maret, 2023)
Interpersonal meaning has important role in communication to achieve good connection among the speaker and the hearer. There are many ways in realizing interpersonal meaning, one of which is by investigating mood and modality used. Consequently, this study aims to analyze the mood and modality types identified in Taylor Swift’s speech at New York University. This study applies systemic functional linguistics in terms of interpersonal meaning proposed by Halliday and Matthiessen (2014). This study also implements qualitative method to answer the problems of the study which taken from Taylor Swift’s utterances during her speech contained mood and modality types as the data. However, the writers use data analysis technique by Miles and Huberman (1994). As the result, there are 195 clauses indicated as mood types which are divided into three types. There are 173 clauses classified as declarative mood types which made it the most frequently used by the speaker. Besides, there are 55 clauses categorized as modality types by making the modalization type as the dominant clause occured in the speech with the occurrences of 32 clauses.